ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR MATEMATIKA PADA MATERI STATISTIKA SISWA SMK KB - Deasy Kartikasari; Isnurani Isnurani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research is useful to see the results of the binary regression model and provide an overview of the factors that influence student learning difficulties in the statistics material at SMK KB. This study uses a type of quantitative research with survey methods. The population was taken from data from class XII students of Gema Bhakti 1 Jasinga Vocational School with the samples used, namely class XII A and class XII B. The collection of research data was obtained using questionnaires, interviews, and observations. The questionnaire contains independent variables (X) in the form of factors that influence learning difficulties in statistical material with independent variables: (X1) independent learning, (X2) learning motivation, (X3) family environment, (X4) school environment, (X5 ) learning facilities and for the variable (Y) the average test scores in statistics. The data analysis technique is a binary logistic regression method. After the analysis showed that the learning motivation factor (X2) in statistical material had a significant effect on students' learning difficulties at SMK KB. Whereas (X1) learning independence, (X3) family environment, (X4) school environment, and (X5) learning facilities in the learning difficulties of students of Gema Bhakti 1 Jasinga Vocational School on statistics material has no significant effect